2023
DOI: 10.4018/978-1-6684-8504-0.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Competence at Schools

Alexandros Argyriadis,
Efthymia Efthymiou,
Agathi Argyriadis

Abstract: Recent research highlights the extraordinary significance of educational leadership for the motivation of teachers about the development of inclusive rationale in the school context. At the same time, due to the increased incidents of violence at schools, the need for inclusion of vulnerable groups seems to be constantly rising, as well as the need to develop cultural competence in both teachers and the student population. The purpose of this study was to measure the cultural competence of educational leaders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that although teachers may have some knowledge and awareness of diversity issues, there is still a need for more comprehensive and ongoing professional development in this area (Kwok, 2020). In particular, teachers may benefit from more specific training on the histories and experiences of diverse groups, as well as strategies for creating inclusive classroom environments (Argyriadis et al, 2023a). Additionally, it is important for teachers to recognise and actively address their own biases and stereotypes, as these can have a significant impact on learner outcomes (Cohen & García, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that although teachers may have some knowledge and awareness of diversity issues, there is still a need for more comprehensive and ongoing professional development in this area (Kwok, 2020). In particular, teachers may benefit from more specific training on the histories and experiences of diverse groups, as well as strategies for creating inclusive classroom environments (Argyriadis et al, 2023a). Additionally, it is important for teachers to recognise and actively address their own biases and stereotypes, as these can have a significant impact on learner outcomes (Cohen & García, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, inclusive education requires of these teachers to possess a special set of competencies that were not previously part of their initial training (Blanton et al, 2011;Kuyini et al, 2021). These key competencies include the essential skills, abilities and knowledge to teach in a way that meets the needs of each learner in a mainstream classroom (Argyriadis et al, 2023a;Florian, 2009;Hornby 2010), making educators able to design the educational process with greater flexibility adapting the learning objectives, the content, the materials and the environment, depending both on the different characteristics of the individual students and the whole classroom dynamics (Ainscow & Goldrick, 2010). The difficulties that educators face nowadays stem not only from the presence of special educational needs and/or disability (SEND), but also from other forms of diversity, including ethnic and cultural diversity, taking into account the effects of the current refugee surge (Samsari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%